2014
DOI: 10.4162/nrp.2014.8.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Pear pomace water extract inhibits adipogenesis and induces apoptosis in 3T3-L1 adipocytes

Abstract: Obesity occurs when a person's calorie intake exceeds the amount of energy burns, which may lead to pathologic growth of adipocytes and the accumulation of fat in the tissues. In this study, the effect and mechanism of pear pomace extracts on 3T3-L1 adipocyte differentiation and apoptosis of mature adipocytes were investigated. The effects of pear pomace extract on cell viability and the anti-adipogenic and proapoptotic effects were investigated via MTT assay, Oil red O staining, western blot analysis and apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…have been reported (Rabetafika et al ., ). It has been found that besides dietary fibre, pear pomace contains valuable substances with healthy effects on our metabolism, such as phenolic compounds and organic acids, among others (Rhyu et al ., ). Because of its composition, PP has been investigated with different medical objectives.…”
Section: Introductionmentioning
confidence: 97%
“…have been reported (Rabetafika et al ., ). It has been found that besides dietary fibre, pear pomace contains valuable substances with healthy effects on our metabolism, such as phenolic compounds and organic acids, among others (Rhyu et al ., ). Because of its composition, PP has been investigated with different medical objectives.…”
Section: Introductionmentioning
confidence: 97%
“…Obesity is a major risk factor for many metabolic disorders such as hyperlipidemia, diabetes mellitus, hypertension, atherosclerosis and cardiovascular diseases (Rhyu et al, 2014). Adipocytes play a crucial role in the regulation of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity refers to excess accumulation of triglycerides in our body due to imbalances between energy intake and expenditure. Obesity is the main risk factor for coronary artery disease by generating adipocytes (hyperplasia) as well as increasing their cell size (hypertrophy) (Wang & Cho, 2011), and a major cause of diabetes, hypertension, hyperlipidemia, and inflammatory and metabolic disorders (Rhyu et al, 2014). The World Health Organization (WHO) requires intensive, worldwide management of obesity because of its seriousness (Wang & Cho, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the pears produced in South Korea are Asian Pears, harvested in Naju, Jeollanam-do, South Korea. Pears contain high sugar and water, and there are plentiful antioxidative polyphenol substances especially on pear skin, such as arbutin, epicatechin, coumaric acid, caffeic acid, catechin, and chlorogenic acid (Rhyu et al, 2014). The edible part of pears contains sugar, largely in the form of fructose rather than glucose, and has less organic acid, resulting in less sour taste than in an apple.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation